PHYSICAL ATTRIBUTES OF SOIL IN INTERCROPPED SYSTEM AND MONOCULTURE OF PASSION FRUIT (Passiflora edulis sims) - Ramos, A. M. R.; Amorim, B. M. B.; Freire, C. T. M.; Lima, D. L. F. A. (Revista Brasileira de Engenharia de Biossistemas, 2019)
The quality of the soil is directly related to the use and the system of cultivation adopted by the producers. The objective of this manuscript was to evaluate the influence of intercropped and monoculture passion fruit cultivation on soil physical attributes (bulk density, total porosity and hydraulic conductivity) in Latossolo Vermelho-Amarelo distrófico (Oxisol) in the Municipality of Palmas, Tocantins. For the data analysis, statistical techniques of multivariate analysis were used, since it allows to evaluate a set of data and evidence independent results. As a result it was obtained that the first component was responsible for capturing 74% of the data variance. Although no significant differences were verified (T test performed in the ACP 1, 2 and 3) between the two evaluated treatments, there is a trend of segregation between treatments in the ordering diagram. In this first year of study it can not be concluded that the intercropping improved the physical quality of the soil.